La Ilegalidad: una herramienta de análisis para la naturaleza del conflicto en Colombia (2013)
For many theorists on peace, find answers to the problem: How to Overcome the war? Converge its multiple areas that can and do seek to answer that question, however a response would be in human nature and the nature of the conflict. For Colombia, find analysis tools that lead to ending the conflict, uses elements beyond the internal politics and the struggle of the state against illegal groups, this is illegal, which is therefore within the culture of violence as defined by Johan Galtung. From these disparate theories of the causes of war, we can address the issue of how to achieve greater peace in Colombia. From the above, the main objective of this article is to build a model for peace, but to analyze important elements that occur within the conflict and are analyzed from events undertaken at certain times in the history of the conflict. The main conclusion is that in Colombia the premium nature of conflict and violence culture that breeds violence with lawlessness in society also draws its legitimacy along with drug trafficking, gangs, insurgency in Colombia today for a easy way to economic and social problems it faces.